2016
DOI: 10.1016/j.jprot.2016.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Comparative leaf proteomics of drought-tolerant and -susceptible peanut in response to water stress

Abstract: Peanuts (Arachis hypogaea L.) are a major source of plant protein grown in subtropical and tropical regions of the world. Pre-harvest aflatoxin contamination is a major problem that affects peanut crop yield and food safety. Poor understanding of molecular and cellular mechanisms associated with aflatoxin resistance is largely responsible for the lack of progress in elucidating a process/methodology for reducing aflatoxin contamination in peanuts. Drought perturbs the invasion of the aflatoxin producing fungus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 74 publications
(62 reference statements)
3
39
0
Order By: Relevance
“…g ., [99, 102103]). Others have confirmed a drought-induced elevation of their levels for drought-tolerant genotypes but observed decreased amounts of these proteins in drought-susceptible genotypes [104], or a decrease in plants showing a higher susceptibility to water deficiency and no changes in plants that are resistant to this stressor [96]. There are also studies reporting a down-regulation of LHC proteins both in drought-resistant and sensitive genotypes [112, 114] or an increase of levels of some LHC proteins, a decrease of others in a genotype with a lower susceptibility to drought conditions, but no changes in a highly susceptible genotype [119].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…g ., [99, 102103]). Others have confirmed a drought-induced elevation of their levels for drought-tolerant genotypes but observed decreased amounts of these proteins in drought-susceptible genotypes [104], or a decrease in plants showing a higher susceptibility to water deficiency and no changes in plants that are resistant to this stressor [96]. There are also studies reporting a down-regulation of LHC proteins both in drought-resistant and sensitive genotypes [112, 114] or an increase of levels of some LHC proteins, a decrease of others in a genotype with a lower susceptibility to drought conditions, but no changes in a highly susceptible genotype [119].…”
Section: Discussionmentioning
confidence: 99%
“…Various authors have described a decrease in the levels of this protein in the leaves of some drought-sensitive genotypes but an increase, no changes or at least a more gradual decrease in a corresponding drought-resistant genotype [9899, 104, 107, 112114]. However, others did not find genotypic differences in the drought-induced changes in this OEC component [101, 115116].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional annotation of proteins was conducted using Gene Ontology (GO) annotation [25]. The differentially accumulated proteins were assigned to the Cluster of Orthologous Groups of proteins (COG) database and the Kyoto Encyclopedia of Genes and Genomes (KEGG) database [26].…”
Section: Methodsmentioning
confidence: 99%
“…For instance, analyses of peanut ( Arachis hypogaea L.) varieties with contrasting tolerance to water deficit have shown a relation between plant tolerance to the stress and the abundance of proteins involved in stress signaling and wax biosynthesis in leaves (Kottapalli et al, 2009). A similar approach was taken by Katam et al (2016) who identified proteins related to nitrogen metabolism, defense and cellular biogenesis exclusively in the tolerant peanut cultivar. Abiotic stress responses in a major legume crop like soybean have been reviewed elsewhere (Hossain et al, 2012, 2013; Hossain and Komatsu, 2014; Komatsu et al, 2015).…”
Section: Proteomics As a Tool To Identify Stress Responses In Legumesmentioning
confidence: 99%